Evaluasi Kebijakan Peraturan Pemerintah No. 17 Tahun 2010 tentang Pengelolaan dan Penyelengaraan Pendidikan (Studi Kasus Evaluasi Pengelolaan dan Penyelenggaraan Pendidikan Khusus bagi Penyandang Cacat dan Kelainan) - Meitisa Vanya Simanjuntak; Maesaroh Maesaroh; Slamet Santoso (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2014)
Education is recognized as a fundamental right of citizens in the life of the nation. Every person has the right to receive educational services and guarantee for education of the country. Therefore, the State was required to meet the needs and education for its citizens including those with disabilities and disorders / disabilities. Policy on the Management and Operation of Education is one policy that can guarantee the implementation of special education for the disabled and functional abnormalities that provide educational services for students who have difficulty in following the learning process due to physical, emotional, mental, intellectual, and / or social . The objectives are to develop the potential of learners optimally within its capabilities.This study aims to determine the performance management policy and the implementation of special education for persons with disabilities and abnormalities in Semarang in accordance with Government Regulation no. 17 of 2010 with the wear indicators of evaluation: Input, Process and Output as well as the use of education as a national standard 8 operationalization of the concept under study. In addition, this study also aimed to describe the obstacles as well as solutions in the management of policy implementation and delivery of special education in the city of Semarang.The results showed that the management and operation of Semarang city still has many shortcomings which can be seen from: Standard contents are less rigid and less accommodating ABK special talents, Standards Educators and education personnel who still have not managed properly related to the existence and adequacy, Standard infrastructure is still below the minimum service standards for the types of special schools. Financing is still lacking in terms of financing physical, educational outcomes assessment standards are still only show the results of the students at this stage of cognition, as well as graduate competencies are still lacking in terms of skill. The jug is affected by the shortage of regulations is still not clear which affect the management and administration in the city of Semarang. Recommendations from this research is that the delegation of authority immediately held a special education management as a whole to the Provincial Government of Central Java, reviewing and preparing content standards are more adaptive and able to accommodate special talents ABK, manage and commercialize infrastructure better, perform mapping needs and shortages of teachers and and spreading, select and define the mechanisms, procedures and assessment instruments are able to describe the knowledge, attitudes and skills, and provide support for public order management and delivery of special education, especially parents of children with special needs such .